A bibliometric review on a co-pyrolysis of biomass and plastic waste (Research, Society and Development, 2019)
Economic growth challenges the security of the energy matrix in meeting the energy demand of society. In addition to environmental risks, fossil fuels are increasingly unable to meet this demand, and research by renewable sources is leveraged. Within this context, recent studies on co-pyrolysis, a technique that promotes the reduction of waste volume and the generation of compounds with high value, are gaining notoriety With the objective of evaluating the maturity of these studies and the formation of a specific database on the subject, a bibliometric revision was used as a tool, which allows the selection of articles within a database based on statistical parameters, such as number of citations and impact fator. Therefore, it can be concluded that, although recent, co-pyrolysis presents as a promising technique, simple and low cost, for the improvement of the yield and structural composition of pyrolysis products.